Spatial Distribution of Chromium Metal in Water and Sediment in the Berbek Industrial Area, Sidoarjo Regency - Fitrianah, Listin; Purnama, Agus Rachmad (Jurnal IPTEK, 2022)
Berbek Industrial Estate is the largest industrial area in Sidoarjo Regency. The most dominant concentration of heavy metals in industrial areas is chromium in water and sediments in rivers which have the potential to have a negative impact on humans, this is because rivers are a place for developing aquatic organisms including fish that are consumed by local residents. Parameters include chromium content in river water and sediment. Spatial distribution analysis uses the kriging method on laboratory results and overlay to describe the distribution map. The result of the highest content in water parameters is the location of Gedongan Village at 0.31 ppm. Based on Peraturan Pemerntah Republik Indonesia Nomor 82 Tahun 2001 on Water Management and Pollution Control, states that the environmental quality standard for chromium in class III rivers is 0.05 mg/L. The highest content in sediment is the Berbek location at 3.24 ppm.